STUDY OF MILLET ULTRA-EARLY MATURING VARIETIES IN POST-CUTTING AND POST-REAPING CROPS DEPENDING ON PREDECESSORS AND METHODS OF SOWING - Shevnikov, M. Y.; Tyshchenko, V. M.; Kostenko, M. P. (Scientific Progress & Innovations, 2021)
The results of researching the cultivation of millet ultra-early maturing varieties in post-cutting and post-reaping crops are presented. Thus, two profits per year can be received. The article analyzes the weather conditions during the study, phenological observations, plant density, vegetative weight and structural analysis. August was the hottest month during the experiment, and no precipitation was observed in October. The varieties sown in fallow land were the first to emerge and ripen. The highest density after germination was in Bila Altanka variety – 427 plants/m2 sown in fallow land by row seeding method; before harvesting Zolushka variety sown by row seeding method amounted to 261 plants/m2 after winter wheat. Bila Altanka variety sown in fallow land by row seeding method had the largest vegetative weight. The maximum number of leaves was in Zolushka variety sown by row seeding method after winter wheat – 1,683 pieces per m2. The maximum plant height before harvesting was in Bila Altanka sown in fallow land, and in the tillering phase also in Bila Altanka, but the predecessor was pea. The panicle length in some way depends on the plant height, so in plants where fallow land was the predecessor, the average plant height was the largest and, accordingly, the largest average panicle length. Post-reaping crops had a better effect on the soil, because the empty field left after early crops is exposed to negative factors. In Ukraine, the main direction of millet cultivation is fodder production, so the cultivation of crops in fodder crop rotation provides green fodder for animals throughout the warm period. 40 million hectares is the area occupied by millet crops in world agriculture. In general, the area of millet crops in the world is increasing. In Ukraine, in Zaporizhia, Kharkiv, Kherson, Mykolaiiv, and Dnipropetrovsk regions, the largest gross yields of millet grain are received because there are the best conditions for growing millet in these regions, while in western Ukraine, millet sown areas are limited. Steppe and Forest-Steppe zones of Ukraine are the most spread for millet cultivation. Despite the value of this crop, its sown areas in Ukraine are insignificant.